(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
Extended spectrum beta-lactamase (ESBL) producing organisms pose unique challenges to clinical microbiologists, clinicians, infection control professionals and antibacterial discovery scientists. The study was done to determine ESBL producing strains by a most feasible and accurate phenotypic method. Urine, surgical wound swab, burn wound swab and pus samples were taken from Sir Salimullah Medical College and Mitford Hospital and from Burn Unit of Dhaka Medical College Hospital from January 2011 to December 2011. ESBL producers were detected by Double Disc Synergy Test. From 354 different samples, 59.04% organisms were isolated. Among them 89% were Gram-negative organisms. Out of these Gram-negative organisms 41.40% isolates were ESBL producers. Among them 75% were Klebsiella spp. and 41.67% were Esch coli. This study shows that the frequency of ESBL producing strains of Esch. coli and Klebsiella spp. is high in both hospitals and it has a significant inference for patient’s management. Hence, it is very important that a doctor should be familiar with the clinical significance of these enzymes and potential strategies for dealing with this growing problem. DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19330 Bangladesh J Med Microbiol 2013; 07(02): 21-24